Mas̱navī soz va gudāz - Šauq Nīmvī,Ašrafī, Vahāb (Ejūkešnal Pablišing Hāʾūs, 2012)
Poems; includes editorial introduction
Poems. - In arab. Schrift, Urdu. - Title on t.p. verso in roman: Masnavi soz-o-gudaz
Keywords: Masnavis; Urdu